Challenges and prospects for sorting and disposing of household solid waste: a case study of a recycling cooperative in Minas Gerais, Brazil - Villela Carvalho, Marcella (2025)
Introduction: This article discusses solid waste generation and the importance of waste picker organizations and cooperatives in Minas Gerais, Brazil. Objective: From this perspective, the general aim of the research was to evaluate and propose improvements to the sorting and final disposal of household waste collected by a recycling cooperative. Methodology: The study consisted of bibliographical research and field research. It was a quantitative, observational case study using a questionnaire for managers and cooperative members. The gravimetric composition observed in 2019 and 2020 and from January to July 2021 was obtained by consulting the cooperative's data. Results: The results showed that there was an increase in the generation of household waste over the years analyzed. The results indicated that in 2019, the most extensive collections were of cardboard waste (290,987 kg), glass (172,760 kg), and white paper (128,582 kg), which accounted for 63.6% of the collection. The total collection during this period was 931,557 kg. In 2020, the largest collections were of cardboard waste (283,334 kg), glass (254,220 kg), and white paper (135,873 kg), which accounted for over 69% of the collection. The total collection during this period was 969,565 kg. From January to July 2021, the total collection was 527,632 kg. Conclusion: The increase in waste generation over the years indicates the demand for an increase in the hiring of cooperative members responsible for sorting waste and implementing more robust environmental education programs to promote awareness of proper waste disposal practices.